PERLINDUNGAN HUKUM TERHADAP PEMILIK HAK ATAS TANAH YANG TELAH DITERBITKAN SERTIPIKATNYA ATAS NAMA PIHAK LAIN (Studi Pada Sertipikat Hak Milik Nomor 1.022 di Kecamatan Tarutung, Kabupaten Tapanuli Utara) - KIKI RATNA PATRICIA SIREGAR (PREMISE LAW JURNAL, 2015)
The position of the Letter of Notification of Land is legally used as the recommendation to request for land certificate. The Letter of Notification can give evidence that the land has been tilled by the owner and the case has been acknowledged by the other tillers and strengthened village head, and subdistrict head. The problems of the research were as follow Certificate No. 1.022 could be issued on another person's land at Aek Ristop, Kelurahan Hutatoruan VII Tarutung Subdistrict. North Tapanuli. The research used judicial empirical approach with descriptive analytic as its specification. The data were gathered by conducting field research The result of the research showed that by government officials from village, subdistrict. until the Land Office has violated law and good government principles. and why due diligence and carefulness. The research was that the issuance of the Proprietary Rights Certificate No.1.022 was invalid as follows: the factor of the authority that issued the certificate, the factor of lhe applicant's bad faith by hiding the judicial data, thirdly, the factor of ambiguity of the origin of Ihe land so that the mapping of registering the land in the Land Office is incomplete, In consequence, the certificate is legally and administratively defective and the certificate holder does not get legal protection. Keywords: Legal Protection, Land Rights Owner, Certificate